2016
DOI: 10.1111/bjh.14303
|View full text |Cite
|
Sign up to set email alerts
|

Sevuparin binds to multiple adhesive ligands and reduces sickle red blood cell‐induced vaso‐occlusion

Abstract: SummarySevuparin is a novel drug candidate in phase II development as a treatment for vaso-occlusive crises (VOC) in patients with sickle cell disease (SCD). As a heparin-derived polysaccharide, sevuparin has been designed to retain antiadhesive properties, while the antithrombin-binding domains have been eliminated, substantially diminishing its anticoagulant activity. Here, we demonstrate that sevuparin inhibits the adhesion of human sickle red blood cells (SS-RBCs) to stimulated cultured endothelial cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 84 publications
0
28
0
Order By: Relevance
“…Facilitating rapid de-sequestration has also been suggested as a therapeutic mode of action for severe malaria, with recent clinical testing of the anti-rosetting compound sevuparin [90]. One could hypothesize that a compound that blocks sequestration keeps parasites in the vasculature and thus increases the ability of both the spleen and the immune system to clear these.…”
Section: Severe Malariamentioning
confidence: 99%
“…Facilitating rapid de-sequestration has also been suggested as a therapeutic mode of action for severe malaria, with recent clinical testing of the anti-rosetting compound sevuparin [90]. One could hypothesize that a compound that blocks sequestration keeps parasites in the vasculature and thus increases the ability of both the spleen and the immune system to clear these.…”
Section: Severe Malariamentioning
confidence: 99%
“…Sevuparin is a low-anticoagulant heparin analog from which the high-affinity antithrombin III-binding pentasaccharide has been removed, resulting in a lack of direct effect on factor Xa and thrombin. Sevuparin was developed to prevent vaso-occlusion in patients with malaria and sickle cell disease, in which the mode of action is to inhibit aggregation of erythrocytes (13,14). Here, we show that sevuparin attenuates neutrophil-induced hyperpermeability and lung edema without inhibiting neutrophil accumulation in lung tissue.…”
mentioning
confidence: 73%
“…However, well-designed placebo-controlled studies with different LMWH, and enrolling participants with different genotypes of sickle cell disease are lacking 50. Telen et al51 demonstrated that sevuparin, a heparin-derived polysaccharide, reduced sickle cell related VOC’s. The efficacy of sevuparin is believed to be due to its anti-adhesive properties, as it binds to P-and L-selectins, TSP, fibronectin, and VWF, all of which are involved in the sickle cell VOC’s.…”
Section: Discussionmentioning
confidence: 99%